Fungsi Representasi Ideologi Kekuasaan dalam Tuturan Mata Najwa Bertema Politik - Siti Shofi Ima; Dawud Dawud (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: This research is focused on studying the function of ideological representation in political theme utterances of "Mata Najwa". The approach in this research is qualitative using the analysis critical discourse perspective (CDA) by Norman Fairclough in order to represent the ideology that is reflected inside the utterances. The data in this study are in the form of words, phrases, clauses, and sentences inside the political theme utterances of “Mata Najwa”. The data source in this study is political theme utterances of Mata Najwa. The data was collected by using an observation method. The procedure of data analysis is carried out by downloading the target data, transcribing data, identifying data, presenting data based on research focus, and having the conclusion. The results of this research such as (1) the function of ideological representation for maintaining power can be divided into the ideological representation in order to provide support, the ideological representation in order to deliver positive information, and the ideological representation in order to create a positive opinion (2) the function of ideological representation in order to oppose against power can be divided into the ideological representation in order to criticize, the ideological representation that has a different point of view, and the ideological representation in order to create a negative opinion (3) The function of neutral ideological representation can be divided into the ideological representation in order to convey information based on facts, the ideological representation in order to compare statements, and the ideological representation in order to ask for information. Keywords: the ideological representation, utterances, power, the “Mata Najwa” show Abstrak: Penelitian ini difokuskan pada kajian fungsi representasi ideologi kekuasaan dalam tuturan Mata Najwa bertema politik. Pendekatan dalam penelitian ini adalah kualitatif dengan perspektif analisis wacana kritis Norman Fairclough untuk merepresentasikan ideologi yang terdapat dalam sebuah tuturan. Data dalam penelitian ini berupa kata, frasa, klausa dan kalimat yang terdapat dalam tuturan acara Mata Najwa bertema politik. Sumber data dalam penelitian ini adalah tuturan dalam tayangan Mata Najwa bertema politik.  Pengumpulan data dilakukan dengan metode simak. Prosedur analisis data dilakukan dengan mengunduh sumber data, mentranskrip data, mengidentifikasi data, menyajikan data sesuai dengan fokus penelitian dan penarikan kesimpulan. Hasil penelitian ini meliputi (1) fungsi representasi ideologi untuk mempertahankan kekuasaan dapat dibedakan meliputi representasi ideologi untuk memberikan dukungan, representasi ideologi untuk memberikan informasi positif, dan representasi ideologi untuk menciptakan opini positif (2) fungsi representasi ideologi untuk melawan kekuasaan dapat dibedakan meliputi representasi ideologi untuk mengkritik, representasi ideologi yang memiliki sudut pandang berbeda, dan representasi ideologi untuk menciptakan opini negatif (3) fungsi representasi ideologi yang bersifat netral dapat dibedakan meliputi representasi ideologi untuk menyampaikan informasi berdasarkan fakta, representasi ideologi untuk membandingkan pernyataan, dan representasi ideologi untuk menanyakan informasi. Kata kunci: representasi ideologi, tuturan, kekuasaan, Mata Najwa